STUDI PENGARUH PERUBAHAN POTENSIAL GRAVITASI BIMASAKTI TERHADADAP EVOLUSI ORBIT DAN SEJARAH PEMBENTUKAN BINTANG PADA SATELIT GALAKSI - Elian Diva, Alfania
The orbit evolution of satellite galaxies around the Bimasakti is influenced by the gravitational potential of the bulge, disc, and halo component of Bimasakti. Study about galaxy formation shows that galaxies in universe experience mass change through merging with another galaxy and dark matter accumulation. The growth of the mass indicates there is gravitational potential change on galaxies including Bimasakti with respect to time. Numeric integration toward motion equation is done using Galpy package applicated on python to track the orbit evolution of satellite galaxy samples around Bimasakti. The data needed for the integration are position, radial velocity, and proper motion of each sample from Gaia DR2. Integration was applied to the static and time-dependent potential model. Analysis was done through literature study to find out processes related to star formation history in satellite galaxies that were influenced by their orbit evolution. The results are star formation in dwarf spheroidal galaxies (dSphs) more influenced by tidal interaction with Bimasakti and ram pressures from halo Bimasakti. Different from luminous dSphs, star formation in the dimmer dSphs (UFDs) are more likely to be influenced by the reionization in the young aged universe.